Tindakan Hipokrit Terhadap Kondom dalam Dinamika Hubungan Sosial (Studi Kualitatif Pada Masyarakat Kota Makassar) - Andi Agustang; Adam Badwi; Andi Tenri Pada Agustang; Rusman Rasyid (Seminar Nasional LP2M UNM, 2019)
This study aims to explore in depth information about why and how hypocritical acts occur towards condoms in the dynamics of social relations in the city of Makassar and theoretical solutions that can be developed to eliminate hypocritical actions towards condoms. This research method is qualitative by using a hermeneutic-phenomenological approach which data is collected through in-depth interviews with 8 key informants that obtained through snowball sampling technique. The results of this study indicate that individual hypocritical actions towards condoms are caused by religious norms, cultural values and previous experience in using condoms. The theoretical solution offered in an effort to change hypocritical actions to become non-hypocritical towards using condoms is the formation of individual understanding through the institutionalization of local wisdom as one of the medical devices as the same with other medical devices in the dynamics of social relations.